2020
DOI: 10.32348/1852.4206.v12.n3.25159
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficacia en la vida académica y rasgos psicopatológicos

Abstract: El objetivo del presente trabajo fue explorar la existencia de diferencias significativas en autoeficacia en la vida académica entre sujetos con rasgos psicopatológicos y sujetos que no presentan rasgos psicopatológicos en el contexto universitario mexicano, utilizando la Escala de Autoeficacia en la Vida Académica (EAVA) y el Inventario Multifásico de Personalidad de Minnesota (MMPI-2). La muestra estuvo compuesta por 251 estudiantes universitarios. Considerando los antecedentes, los sujetos con rasgos psicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…15(2), 75-94 https://doi.org/10.37708/psyct.v15i2.664 taking into account that people deploy adaptive, functional or dysfunctional strategies which enable them to succeed or fail in everyday life situations. (García-Méndez & Rivera-Ledesma, 2020). Therefore, the study of general self-efficacy and related factors is becoming increasingly relevant in the educational context, since this information could be used to achieve academic success, an effective approach to the educational process, and an improvement in the quality of life of students (Morales-Rodriguez & Pérez-Mármol, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…15(2), 75-94 https://doi.org/10.37708/psyct.v15i2.664 taking into account that people deploy adaptive, functional or dysfunctional strategies which enable them to succeed or fail in everyday life situations. (García-Méndez & Rivera-Ledesma, 2020). Therefore, the study of general self-efficacy and related factors is becoming increasingly relevant in the educational context, since this information could be used to achieve academic success, an effective approach to the educational process, and an improvement in the quality of life of students (Morales-Rodriguez & Pérez-Mármol, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the educational context, several studies in have shown that self-efficacy is positively related to academic goals and achievement motivation (Valle et al, 2015), reflective learning styles (Laffita & Guerrero, 2017), metacognition (Taghani & Razavi, 2021), productive coping styles (Piergiovanni & Depaula, 2018), flow and engagement (Mesurado et al, 2015), self-concept and psychological well-being (Veliz-Burgos & Apodaca, 2012). While, on the other hand, it is negatively related to academic stress (Jersusalem & Mittag, 2009), substance addictions in adolescents (Marlatt et al, 2009), school failure (Lata & Nasa, 2014), anxiety, neuroticism, somatization, depression, hostility, phobias, paranoid thinking and psychoticism (García-Méndez, & Rivera-Ledesma, 2020), among other variables related to mental health.…”
Section: Psychological Thoughtmentioning
confidence: 99%
“…In this regard, there are several studies that highlight various explanatory factors of self-efficacy, depending on the gender of students and their cognitive abilities (Vasile et al, 2011), the nationality of students, mediated by their sociocultural differences (Steca et al, 2009;Mesurado et al, 2015); personality traits (García-Méndez, & Rivera-Ledesma, 2020;Stajkovic et al, 2018) and self-concept (Merino & Díaz, 2003). In this regard, Bandura (1993) explained that students' beliefs in their own abilities have effects on their academic performance and vocational decisions, since self-efficacy is a determinant in the processes of self-regulation of learning and the use of metacognitive strategies, necessary for the academic orientation of cognitive functioning.…”
Section: Psychological Thoughtmentioning
confidence: 99%
“…Al respecto, Piergiovanni y Domingo (2018) tomando las premisas de Bandura (1997), aseveran que las creencias de autoeficacia influyen sobre las acciones que las personas deciden llevar a cabo, sobre la perseverancia, los fracasos situacionales, y sobre el afrontamiento al estrés. Un fuerte sentido de autoeficacia puede ayudar a combatir eficientemente el estrés y propiciar un sentimiento de bienestar (García-Méndez & Rivera-Ledesma, 2020), hallazgos que no se corroboran con lo obtenido.…”
Section: Religacion Revista De Ciencias Sociales Y Humanidadesunclassified
“…Estudios realizados revelaron que relaciones significativas y negativas entre autoeficacia y depresión, así como de la autoeficacia con pensamientos negativos. Se examinaron un grupo de estudiantes noruegos de ambos sexos, a fin de evaluar si aquellos que habían reportado síntomas severos de problemas de salud mental, tenían un mayor riesgo de padecer una baja autoeficacia; los resultados comprobaron la hipótesis al encontrarse una fuerte asociación entre síntomas severos de alteraciones en la salud mental con una baja autoeficacia (García-Méndez & Rivera-Ledesma, 2020).…”
Section: Religacion Revista De Ciencias Sociales Y Humanidadesunclassified